Qualitative Analysis of Darlington Feedback Amplifier at 45nm Technology - Rashmi Singh; Rajesh Mehra (Bulletin of Electrical Engineering and Informatics, 2018)
The transistors are the key element of present communication system having high data rate. Some applications need high gain by using very low frequency, and then transistors are used. Amplifier is the key element in many applications of present high data rate communication system such as low noise amplifier (LNA), broadband amplifier, distributed and power amplifier. The Darlington pair amplifier is analyzed for high frequency performance and related effect of bandwidth. Broadband feedback Darlington pair amplifier is designed with enhanced gain, bandwidth and slew rate. This paper presents the comparison of single stage and three stage feedback Darlington feedback amplifier with reference to gain, bandwidth and slew rate. This paper is simulated on cadence analog design environment at GPDK 45nm technology. This paper shows that increase in gain, bandwidth and slew rate of three stage Darlington feedback amplifier can show better stability over the single stage Darlington feedback amplifier.